DISTRIBUTION FEATURES OF CURRENT SYSTEM IN NORTHERN CENTRAL VIETNAM COAST (HA TINH - THUA THIEN-HUE) DURING APRIL 2016 - Mau, Le Dinh; Thinh, Nguyen Duc; Tuan, Nguyen Van; Cong, Nguyen Chi; Hoan, Pham Sy; Hoi, Nguyen Truong Thanh; Anh, Vu Tuan; Dung, Nguyen Thi Thuy (Vietnam Journal of Marine Science and Technology, 2018)
This paper presents the modeled results of general current pattern (daily average value) in Northern Central Vietnam Coast (Ha Tinh - Thua Thien-Hue) during April 2016. Study results show that in general, current flowed from the North to the South with small and instable velocity (V ≈ 0.1 - 0.2 m/s). From 2nd to 6th April current flowed from the South to the North. From 7th to 29th April current flowed from the North to the South. During 13rd to 16th April current velocity was weak (V ≤ 0.1 m/s). In the southern region of Thua Thien-Hue province, the direction of current was instable (from 6th to 9th and from 20th to 22nd April current flowed from the South to the North). Current distribution pattern from modeled results was in accordance with the propagation characteristics of surface water temperatures in the studied area through data analysis of satellite images.